Pengaruh E-Service Quality, Brand Image, Dan Social Media Marketing Terhadap Loyalitas Pengguna Dompet Digital Dana Pada Mahasiswa Universitas Telkom Bandung - Pratiwi, Intan; Wardhana, Aditya (eProceedings of Management, 2024)
This research was conducted to determine the influence of e-service quality, brand image, and social media marketingon the loyalty of DANA digital wallet users among Telkom University Bandung students. The aim of this research isto find out and analyze how e-service quality, brand image and social media marketing, both partially andsimultaneously, affect the loyalty of DANA digital wallet users among Telkom University Bandung students. The typeof research used in this research is quantitative research with the sampling technique in this research using accidentalsampling technique. The total sample was 97 students. The analysis techniques used are descriptive statistics andmultiple regression analysis. Based on the research results, e-service quality has a positive and significant influence,brand image has a positive and significant influence, and social media marketing has a positive and significantinfluence. Simultaneously, the variables e-service quality, brand image, and social media marketing have a positiveand significant influence. The conclusion of this research is that the e-service quality and brand image variables ofDANA digital wallet users among Telkom University Bandung students are in the very good category. Meanwhile, thesocial media marketing variable is classified as good. Therefore, DANA can improve social media marketing andmaintain its excellent e-service quality and brand image.Keywords-e service quality, brand image, social media marketing, and loyalty